The Engineering of Chlorinating Device to Disinfect The Conventional Well - Beny Suyanto; Sujangi Sujangi; Sigit Gunawan (Health Notions, 2017)
Well water is one of the main resource of drinking water for the large people, especially for those who do not abonnement of PDAM (The regional corporation which suplies water need). To determine whether the well water physically polluted or not, it can be done by testing the smell, colour and taste. Whereas, to know the level of pollution both chemically and biologically, laboratory test is performed. To purify water from pathogen bacteria, the cause of waterborne deseases, it is necessary to conduct disinfecting activity to make well water safe to drink by the people. This study was experimental research. The purpose of the research was to design a chlorine injection device applied in a conventional well water, to make it safe to consume by the people. The research design was one group pre and post-test design. Then the effectiveness of the function of the device was analyzed by identifying the difference of concentration of the disinfectant (chlorine) to produce chlorine residue, smell, taste and the decrease of colifom bacteria from well water, in line with the standard of Ministry of Health No. 492 /Reg.IV/2010 about the qualification of the quality of drinking water. The result of the research on the dimension of device chlorine injection, in the form of PVC pipe 2 dm³ and 50 cm in length, completed by silicate sand (3 kg). PVC Ø ¾ , cap, doublé screw sock, disinfectant chlorine and the wieght of device is 3,6 kg. Working principle of this device was the putting of chlorine diffusely in the well wáter. The chlorine injection device type A with the chlorine concentration 10.39 g was sable to desinfect well wáter for 6 days with the average chlorine residue 0.212 ppm. While, chlorine injection device type B was able to desinfect well wáter for 16 days by using 20.97 g of chlorine. The capacity of the device was for 1000 L and the device will make the well wáter inodorous, tasteless, and free from coliform bacteria, this is in line with the standard of Ministry of Health No. 492 /Reg.IV/2010 about the qualification of the quality of drinking water. To increase the capacity of function of chlorine injection device, it is important to conduct a testing on well water in rainy season , the volume of water more than 1000 L, the content of chlor in the chlorine, the endurance of the divice, and the different level of pollution. Keywords: Conventional well water, Chlorine residue, Chlorinating